A comparison review of Hehuan flowers and Hehuan bark on the traditional applications, phytochemistry and pharmacological effects. (1st March 2023) - Lu, Pengfei; Zhang, Chengzhong; Zheng, Jiadong; Li, Chunyan; Zhang, Qijin; Huang, Baokang
Abstract: Ethnopharmacological relevance: Albizia julibrissin Durazz is a well-known medicinal plant with the Chinese name Hehuan [合欢]. Hehuan bark and Hehuan flowers have long been recognized as traditional Chinese herbal medicine for treating anxiety, melancholy, insomnia, bruises, pulmonary abscess, fractures, carbuncle, amnesia, acute conjunctivitis, blurred vision, neonatal tetanus and stroke for thousands of years. They are recorded in Chinese Pharmacopoeia separately with different properties. Until now, new chemical constituents and pharmacological activities of Hehuan have been continuously studied and revealed. The aim of the review: This review aims to provide a comprehensive summary of traditional applications, phytochemistry, pharmacology effects, and toxicology of Hehuan bark and Hehuan flowers, and give critical assessment and point out the promising direction for further research on Hehuan. Material and methods: A literature search was undertaken on Hehuan bark and Hehuan flowers by analyzing the information from scientific databases (SciFinder, Pubmed, Elsevier, Google Scholar, Web of Science, and Baidu Scholar). We also gathered the information of Hehuan from classic herbal literatures and conference papers on ethnopharmacology. Results: According to Chinese and English documents, the medicinal history of Hehuan in China can be traced back to ad 25. Meanwhile, its medicinal history as a kind of herbal medicine can also be found in other Asian countries. So far about 140 compounds have been isolated from Hehuan bark and Hehuan flowers, including triterpenoids, flavonoids, lignans, phenolic acids, alkaloids, etc. Among them, flavonoids mainly exist in Hehuan flowers, while Hehuan bark contains lignans and saponins. The composition differences between the barks and flowers of Hehuan account for the different effects and applications. Modern pharmacological studies have indicated that crude extracts and pure compounds of Hehuan flowers and Hehuan bark have multiple pharmacological activities, such as antineoplastic, immunomodulatory, anti-inflammatory, anxiolytic, antidepressant, metabolic regulation, anti-insomnia, neuroprotective, hepatoprotective, sedative, and anti-osteolytic activities. Conclusions: Hehuan ( Albizia julibrissin Durazz) is traditionally used to relieve depression, calm nerves, promote blood circulation and reduce swelling. Modern pharmacological studies have revealed that natural products from Hehuan bark and Hehuan flowers possess extensive pharmacological activities in treating cancer, enhancing immunity, regulating metabolism, improving mental state, etc. These properties make it great clinical application potential. Further research on natural pharmaceutical chemistry, pharmacology, toxicology, pharmacokinetics, and quality standards of Hehuan are still required to verify the efficacy and safety for future clinical applications. Graphical abstract: Image 1 Highlights: Albizia julibrissin (Hehuan) contains rich components and with versatile bioactivities. Hehuan is traditionally used to treat anxiety, melancholy and insomnia for thousands years. Comparison on Hehuan bark and Hehuan and correlation between their pharmacological activities and material basis is presented. Hehuan bark and Hehuan flowers are safety and effective traditional herbal medicine.